Low-power and High-speed Implementation of Pulse Shaping Filters in Software Defined Radio Receivers - Vinod, A. P.; Lai, Edmund M-K. (Massey University., 2006)
No abstract available
Keywords: Pulse-shaping filter; Software-defined radio; Digital receiver; Digital signal processing